2022
DOI: 10.3390/children9121945
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Monitoring and Factors That May Influence Leg Length Difference in Developmental Dysplasia of the Hip

Abstract: In unilateral Developmental Dysplasia of the Hip (DDH), avascular necrosis (AVN), femoral or pelvic osteotomy, and residual dysplasia causing subluxation of the proximal femur may influence Leg Length Discrepancy (LLD). This can lead to gait compensation, pelvic obliquity, and spinal curvature. The aim of this study is to determine the prevalence of LLD, establish which limb segment contributes to the discrepancy, describe how AVN influences LLD, and ascertain variables that may influence the need for LLD corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Rajiv M. Merchant once mentioned that in children with unilateral DDH, the growth of femur was the main factor that causes the difference in Leg Length Discrepancy (LLD). When the measured length was less than the unaffected side, the shortened part mainly focuses on the difference of ATD 10 . Some scholars had studied the difference of ATD of hip in children with unilateral SCFE, and thought that the reduction of ATD was a simple and sensitive method for early diagnosis of SCFE, which was better than other classic signs such as Trethowan sign, Loss of epiphyseal height etc 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Rajiv M. Merchant once mentioned that in children with unilateral DDH, the growth of femur was the main factor that causes the difference in Leg Length Discrepancy (LLD). When the measured length was less than the unaffected side, the shortened part mainly focuses on the difference of ATD 10 . Some scholars had studied the difference of ATD of hip in children with unilateral SCFE, and thought that the reduction of ATD was a simple and sensitive method for early diagnosis of SCFE, which was better than other classic signs such as Trethowan sign, Loss of epiphyseal height etc 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that earlier menarche is associated with shorter leg length or lower leg length ratio (Conway et al, 2012). This is because leg growth is more sensitive to hormonal changes than trunk growth during puberty (Merchant et al, 2022). Later menarche allows for more leg growth before reaching adulthood (Zhu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Overgrowth can be stimulated by femoral varus rotational osteotomies for hip reduction [10]. Femoral shortening may be necessary with open reduction of the hip with a delayed diagnosis, or it can be secondary to femoral head collapse from avascular necrosis [6]. Limb length discrepancy, that is, shortness, can be expected in hips with severe (Crowe Types III and IV) dysplasia.…”
mentioning
confidence: 99%